The Analysis of Drinking Water Quality in Sumber Agung Village, Kinali District - Sri Reski Wahyuni; Rezi Junialdi; Sanny Edinov; Leila Muhelni (The Future of Education Journal, 2025)
Water is a basic human need in everyday life. Humans use water for daily needs such as drinking, bathing, washing, and so on. Poor quality air will result in a bad environment that will affect human health and safety .Sumber Agung Village has a population of 2,773 people based on infographic data from Sumber Agung Village, consisting of 895 heads of families, with details of 1,411 men and 1,362 women The water source in Sumber Agung Village is PAM water PAM water is an abbreviation of Drinking Water Company, which refers to clean water distributed by drinking water companies to the community through a network of pipes, and has gone through a series of processing processes to ensure its quality is safe and for consumption Experts), stated that PAM air comes from various sources such as rivers, lakes, or groundwater which then go through processing processes such as coagulation, flocculation, sedimentation, filtration, and disinfection before being distributed can be related to several important factors, such as the condition of the air source, the potential for contamination, and its impact on public health. This study aims to analyze the drinking water quality in Sumber Agung Village based on physical parameters. Color: Drinking water should be clear and colorless. Turbidity: Drinking water should not be cloudy, indicating the presence of suspended particles such as mud. Temperature: The ideal drinking water temperature is between 18°C and 22°C. Chemical parameters: pH: The acidity or alkalinity of drinking water should be in the range of 65-85. Biological parameters: Pathogenic bacteria: Drinking water should be free from harmful bacteria such as E. coli and Coliform, according to Health Regulation No. 2 of 2023 concerning Drinking Water Quality Standards.